Quels effets du grand confinement sur la santé et le bien-être des Français ? - Lise Bourdeau-Lepage; Balazs Kotosz (Développement Durable et Territoires)
The Covid-19 pandemic has led the French government to introduce social distancing measures. This article focuses on its effects on the health and well-being of the French people. Based on a survey conducted, during the great lock-down, among a sample of 10,976 French people representative of the French adult metropolitan population, it reveals a deterioration in the state of health of the French, the fall in their level of well-being and differences related in particular to their situation with regard to employment or their housing conditions. The article shows that the level of well-being before lock-down is a factor that plays much more on the evolution of the level of well-being during lock-down than the alteration of the state of health of people.